1998
DOI: 10.1001/archinte.158.7.698
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, Stress, and Genes in Peptic Ulcer Disease

Abstract: The questionnaire and hospital usage data on peptic ulcer disease in the population-based twin cohort suggest that the familial aggregation of the disease is modest, and attributable almost solely to genetic factors. Environmental effects not shared by family members were significant predictors of disease, and they were attributable to smoking and stress in men and the use of analgesics in women. The minor effects of shared environment to disease liability do not support the concept that the clustering of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 28 publications
2
21
1
1
Order By: Relevance
“…This observation is in agreement with previously published epidemiological data [6, 7, 10, 11, 12, 13]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in agreement with previously published epidemiological data [6, 7, 10, 11, 12, 13]. …”
Section: Discussionsupporting
confidence: 94%
“…Why peptic ulcers develop only in the minority of infected persons remains unclear. Various important risk factors for ulcer development have been identified [6, 7, 8, 9, 10, 11, 12, 13]which suggests that the etiology of duodenal ulcer is multifactorial and involves environmental factors, host genetic factors and specific properties of the infecting H. pylori strains. In fact, our and other authors’ recently published results [14, 15, 16]revealed that vacA s1 genotype and cagA+ status of H. pylori were associated with a higher prevalence of duodenal ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, a Finnish nationwide twin cohort study of lifestyle, stress and genes in peptic ulcer disease led to the conclusions that, first, familial aggregation of the peptic ulcer disease is modest and attributable almost solely to genetic factors, and, second, that the data did not support the concept that risk factors such as H. pylori infection could explain familial peptic ulcer disease (Räihä et al 1998). A comprehensive study in Thailand of 70 patients with perforated peptic ulcer compared with a balanced number of control subjects led to the conclusion that stress, but not H. pylori, is associated with peptic ulcer disease in this Thai population (Wachirawat et al 2003).…”
Section: :3mentioning
confidence: 99%
“…Although a substantial percentage of PUD patients have H. pylori, only a small percentage of individuals with H. pylori develop ulceration [9]. Therefore unidentified host characteristics, including genetic influences [10], strain variability and other factors, must play a role in the pathogenesis of PUD [7]. …”
Section: Introductionmentioning
confidence: 99%